2005
DOI: 10.1373/clinchem.2004.044305
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Quantitative Analytical Methods Real-Time PCR for HER-2 Gene Quantification and ELISA of Serum HER-2 Protein and Comparison with Fluorescence in Situ Hybridization and Immunohistochemistry for Determining HER-2 Status in Breast Cancer Patients

Abstract: Background: HER-2 status is generally determined by immunohistochemistry (IHC) or fluorescence in situ hybridization (FISH). Both methods are only semiquantitative, require a tumor sample, and can be difficult to reproduce. We compared these methods with 2 quantitative approaches, one measuring HER-2 gene copy number in tissue by real-time quantitative PCR (qPCR), and the other measuring shed HER-2 protein in serum by ELISA in patients with metastatic disease. Methods: We analyzed 52 cases of metastatic breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 26 publications
(26 reference statements)
7
51
4
Order By: Relevance
“…This discrepancy between RT-PCR and immunohistochemical results can be justified by transcriptional or post-transcriptional activation. PCR false negative result was also shown between quantitative PCR and immunohistochemical methods (Königshoff et al, 2003;Tse et al, 2005). In the other hand, immunohistochemical negative blood sample (26%) and immunohistochemical negative tissue sample (48%) was identified by RT-PCR, in our study.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This discrepancy between RT-PCR and immunohistochemical results can be justified by transcriptional or post-transcriptional activation. PCR false negative result was also shown between quantitative PCR and immunohistochemical methods (Königshoff et al, 2003;Tse et al, 2005). In the other hand, immunohistochemical negative blood sample (26%) and immunohistochemical negative tissue sample (48%) was identified by RT-PCR, in our study.…”
Section: Discussionsupporting
confidence: 60%
“…This study showed no correlation between erb-B2 mRNA expression in peripheral blood and/or tumor tissue and other prognosis factors. In this study, there is not significant correlation between the expression of erb-B2 and tumor size or lymph node in BC patients as mentioned in previous studies (Tse et al, 2005;Youssef et al, 2013).…”
Section: Discussioncontrasting
confidence: 54%
“…Discrepancies of 20-40% from samples evaluated as IHC 2+ with respect to results obtained by using FISH or qPCR techniques have been reported (11,(13)(14)(15)(16)(17). In this study, from fifteen biopsies evaluated as IHC 2+, four (ID 3, 7, 65 and 77) were identified with a <2.0 qPCR ratio, showing non-amplification differences with respect to the negative control (Table I).…”
Section: Resultsmentioning
confidence: 47%
“…This leads to increased serum HER2 ECD concentrations in ϳ30%-40% of patients with metastatic breast cancer and serves as a marker for prognosis and resistance to hormone and alkylating therapy (12)(13)(14). Serum HER2 ECD concentration correlates with tissue HER2 status (by IHC or FISH) (15 ), and the possibility of using it as an alternative to tissue analysis has recently been examined (16 ). In this study, we investigated that possibility further in view of the discordant positive rates between tissue HER2 and serum HER2 in metastatic breast cancer, and we suggest a method that optimizes predictive power of serum HER2 ECD concentration.…”
Section: © 2006 American Association For Clinical Chemistrymentioning
confidence: 99%